2014
DOI: 10.3390/molecules191220929
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Activities of Cinnamon, Geranium and Lavender Essential Oils

Abstract: Acinetobacter sp. represent an important cause of nosocomial infections. Their resistance to some antibiotics, their ability to survive on inanimate surfaces in the hospital environment and their ability to produce biofilms contributes to their virulence. The aim of the study was to determine the antibacterial properties of cinnamon, lavender and geranium essential oils against bacteria of the genus Acinetobacter isolated from several clinical materials and from the hospital environment. A comprehensive evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 24 publications
1
41
0
5
Order By: Relevance
“…Nevertheless, in this study the most effective combination of LEO and OCT decreased the MIC of LEO from 14.86 ± 3.96 mg/mL (1.49 ± 0.4%) to 1.29 ± 0.49 mg/mL (0.13 ± 0.05%). In our previous study, it was also observed that LEO derived from the same production batch exhibited low cytotoxic activity towards HMEC-1 and glioblastoma cell (T98G) lines [29]. IC 50 values of LEO against HMEC-1 and T98G lines were 5.15 µL/mL (4.5 mg/mL) and 2.27 µL/mL (1.99 mg/mL), respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, in this study the most effective combination of LEO and OCT decreased the MIC of LEO from 14.86 ± 3.96 mg/mL (1.49 ± 0.4%) to 1.29 ± 0.49 mg/mL (0.13 ± 0.05%). In our previous study, it was also observed that LEO derived from the same production batch exhibited low cytotoxic activity towards HMEC-1 and glioblastoma cell (T98G) lines [29]. IC 50 values of LEO against HMEC-1 and T98G lines were 5.15 µL/mL (4.5 mg/mL) and 2.27 µL/mL (1.99 mg/mL), respectively.…”
Section: Discussionmentioning
confidence: 84%
“…According to the BP 2013, the major components of LEO are Linalool (20-45 %) and Linalyl acetate (25-47 %). Investigation of the composition of LEO from different regions of the world, have revealed that EOs of Lavender from different locations such as Greece, 22 Italy, 20,44 Poland, 45 Tunisia, 46 South Africa, 21 and Japan 47 were characterized by comparable levels Linalool and Linalyl acetate (2.67 ± 0.53 %) for L-SP (Table 8). Therefore, both samples produced EO in yields greater than the minimum limit of 1.3% specified for L. angustifolia.…”
Section: Morphological Featuresmentioning
confidence: 99%
“…This study used the following ten commercially available essential oils (dr Beta, Pollena Aroma, Nowy Dwór Mazowiecki, Poland): anise, cinnamon, citronella, clove, geranium, lavender, limette, mint, rosemary and thyme. The composition of tested EOs was presented in Table 1 , based on data obtained from previous studies analyzing the EOs’ composition by gas chromatography with flame-ionization and mass spectroscopic detection (GC-FID-MS) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ] or data from European Pharmacopoeia [ 53 ].…”
Section: Methodsmentioning
confidence: 99%